LIVROS: - REA, Editor (Revista Espaço Acadêmico, 2024)
Diário de um Docente: 2019-2021. 1. ed. São Paulo: Editora Patuá, 2023. v. 1. 324p. sossélla sobra silfos. 1. ed. Jundiaí: Telucazu Edições, 2023. v. 1. 112p. Bergman & eu. 1. ed. Guaratinguetá: Penalux, 2024. v. 1. 136p